Where Did They Come From, Where Did They Go: Grazing Fireballs - Shober, Patrick M; Jansen-Sturgeon, Trent; Sansom, Eleanor; Devillepoix, Hadrien; Towner, Martin; Bland, Phil; Cupak, Martin; Howie, Robert; Hartig, Benjamin (IOP PUBLISHING LTD, 2020)
For centuries extremely long grazing fireball displays have fascinated observers and inspired people to ponder about their origins. The Desert Fireball Network is the largest single fireball network in the world, covering about one third of Australian skies. This expansive size has enabled us to capture a majority of the atmospheric trajectory of a spectacular grazing event that lasted over 90 s, penetrated as deep as ∼58.5 km, and traveled over 1300 km through the atmosphere before exiting back into interplanetary space. Based on our triangulation and dynamic analyses of the event, we have estimated the initial mass to be at least 60 kg, which would correspond to a 30 cm object given a chondritic density (3500 kg m-3). However, this initial mass estimate is likely a lower bound, considering the minimal deceleration observed in the luminous phase. The most intriguing quality of this close encounter is that the meteoroid originated from an Apollo-type orbit and was inserted into a Jupiter-family comet (JFC) orbit due to the net energy gained during the close encounter with Earth. Based on numerical simulations, the meteoroid will likely spend ∼200 kyr on a JFC orbit and have numerous encounters with Jupiter, the first of which will occur in 2025 January-March. Eventually the meteoroid will likely be ejected from the solar system or be flung into a trans-Neptunian orbit.